Capital account convertibility : review of experience and implications for IMF policies - International Monetary Fund; Quirk, Peter J. (Washington, DC : International Monetary Fund, 1995)
The study is based on a series of papers prepared for discussion by the IMF's Executive Board in July 1995.
"October 1995."
Includes bibliographical references.
osc 9/8/16
Loans
Keywords: Capital movements